Family Phenotypic Heterogeneity Caused by Mitochondrial DNA Mutation A3243G - Alves, Daniela (2017)
Maternally inherited diabetes and deafness is a rare form of diabetes caused by a mitochondrial DNA mutation. The index case is a 55-year-old woman who was admitted with hypertrophic cardiomyopathy. She had a history of diabetes mellitus and hearing loss. The patient’s mother, two brothers and two sisters also had a history of diabetes and hearing loss. This pattern suggests a maternally inherited disorder. All siblings carried the A3243G mitochondrial DNA mutation. The identification of people with monogenic forms of diabetes mellitus is a diagnostic challenge. This condition should be considered whenever there is a history of diabetes associated with hearing loss and a relevant family history. Cardiopathy is also known to be an important feature of mitochondrial disease. In order to identify this aetiology, family screening, genetic counselling and screening of associated comorbidities are encouraged.